Utilization of computer simulation for detection non-standard situations within single-track lines - Fikejz, Jan; Merta, Jan (Dime University of Genoa, 2019)
This article deals with the use of computer simulation for induction and detection of non-standard/crisis situations within single-track railways. First, attention is paid to the collection and evaluation of historical data, which are then used for the designed simulator. The article then focuses on the design of a simulation tool for inducing non-standard/crisis situations within a monitored segment of a railway network. Simulation tool is then used for selected experiments.
Využití počítačové simulace pro detekci nestandardních situací v rámci jednokolejných tratích
Keywords: Utilization; computer; simulation; for; detection; non-standard; situations; within; single-track; lines; Využití; počítačové; simulace; pro; detekci; nestandardních; situací; rámci; jednokolejných; tratích